Project Based Learning Dalam Meningkatkan Psikososial Anak Di SD Lazuardi Tursina Banyuwangi - Diah Kusuma Wardani; Ali - Priyono (JoEMS (Journal of Education and Management Studies), 2020)
Implementation of Project Based Learning is an explore, evaluate, interpret, synthesize, and information to produce various forms of learning outcomes. Learning that is the source of one's intelligence is his habit to make new products that have cultural value (creativity) and his habit of solving problems independently (problem solving). The child's personal development begins with the development of the child's sensory functions to make observations. SD Lazuardi Tursina Banyuwangi emphasizes the educational process of inculcating positive children's characteristics and life skills, by becoming an educator who always facilitates a comfortable atmosphere for children, always maintains self-esteem and always gives the broadest space- breadth for children to try and wrong (trial and error). From the results of this research, it can be seen that the psychosocial development of children can increase the effectiveness and motivation of student learning when they are in the learning process at school or at home. And it has been feasible Project Based Learning to be used as an additional in improving children's psychic and very helpful effectiveness and efficiency in learning.